The Effect of Psychophysical Pressure and Work Stress on Administrative Staff Productivity through Life Equilibrium as a Mediating Variable - Agam Alfisila; Djoko Soelistya (ADARA, 2026)
Increasing work pressure in the healthcare sector has the potential to reduce employee productivity. This study aims to analyze the effect of psychophysical pressure and work stress on administrative staff productivity with Life Equilibrium as a mediating variable. The study employed a quantitative approach using Partial Least Squares-based Structural Equation Modeling (SEM-PLS). The sample consisted of 80 administrative staff members at Muhammadiyah Hospital Gresik selected through saturated sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using SmartPLS 4.0. The results showed that: (1) Psychophysical pressure and work stress had a significant negative effect on productivity; (2) Both variables significantly negatively affected Life Equilibrium; (3) Life Equilibrium had a significant positive effect on productivity; and (4) Life Equilibrium significantly mediated the effect of psychophysical pressure and work stress on productivity. These findings indicate that despite high work pressure, productivity can be maintained through comprehensive management of work-life equilibrium. The practical implications of this study emphasize the importance of structured workload management policies and psychological support programs to maintain the well-being and performance of administrative staff in hospital settings.